Trends and Developments in Contemporary Zakat Administration - Muhammad, Aliyu Dahiru (Journal of Islamic Economics and Finance Studies, 2024)
Zakat is a third pillar of Islam and has been considered as the mainstay of Islamic economics. It comes at the center of the five pillars of Islam, which some scholars interpret as providing balance between ibadat (worship) and muamalat (day to day human transactions). Historically it provides solutions to economic problems of the Muslims society. However, its application is reduced to individual levels with limited impact in many parts of the world. In the recent times, there is revival of the institution of zakat. Thus, the paper examines the contemporary developments on zakat particularly its potential and applications in Muslim countries and communities. The methodology adopted is content analysis with critical review of the literature. Secondary data were sourced from reports covering 2014 to 2020. The data was specifically analyzed based on the trends and potentials of zakat in Asia, Sub-Saharan Africa, North Africa and the Russian Federation. The paper finds that, zakat in many Muslim jurisdictions has the potential of alleviating poverty and drastically reducing income inequality based on international standards. The implication of the study is that Muslim countries and communities should revive zakat and apply it in their mainstream economic system to solve their socio-economic problems.